PENERAPAN PEMBAGIAN HARTA BERSAMA DI JORONG TIGO SUKU NAGARI PANINJAUAN KECAMATAN X KOTO KABUPATEN TANAH DATAR SUMATERA BARAT (STUDI HUKUM ADAT MINANGKABAU) - Arista Wahyudi; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Minangkabau inheritance law which is part of the customary law that many ins andouts because on one hand Minangkabau inheritance law is a continuation in accordance withthe order of the order according to the law of the mother, but on the other hand, it has to doand influenced by the law of syarak (religion). Among the inheritance in Minangkabau adatis joint property That is all the income of husband and wife during the marriage period (otherthan the property of origin / treasure of gift that follows the origin of the property). In aparent-married society with free marriages of equal status, the joint quest property (apartfrom the original property) can be shared, either because of divorce or the cause ofinheritance.The problems in this research are 1) How is the system of applying the distribution ofcommon property to indigenous peoples in Jorong Tigo Sari Nagari Panihat District KotoKoto Tanah Datar West Sumatra? 2) What is the position of justice in the distribution ofcommon property in Jorong Tigo Suku Nagari Panihat District Koto Koto Tanah Datar WestSumatra? Research method in this research is sociological. The location in this study wasconducted in the region of Jorong Tigo Suku Nagari Panihat District X Koto Tanah DatarWest Sumatra. The population in this study is Indigenous and Ninik Mamak. The data sourceof this research is primary data and secondary data by collecting data through interview,literature study. The data analysis technique used is qualitative.The general description of this research is the general description of customary law.The general description of Adat Law discusses the definition of customary law, the definitionof adat law according to the experts, the basic principles of customary law, the source ofcustomary law, the elements of customary law, and the legal basis for the enactment ofcustomary law.The system of applying the division of common property in Jorong Tigo Nagari PartPanihat in accordance with the provisions of positive law, Compilation of Islamic Law (KHI)and Islamic Shari'a where joint wealth is shared equally, 50% husband and 50% wife. Thejustice of sharing the common property in Jorong Tigo Tribe Nagari Paninjauan, asexplained in the discussion, the distribution of common property has been in accordance withexisting provisions, but its implementation in the community does not run in accordance withthese provisions.Keywords : Customary Law - Joint Property - Justice